Embedding spectrum sharing into LTE-Advanced - McMenamy, Jasmina (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2016)
Society needs more spectrum. It is required to support continuous data growth, a greater number of mobile connections, smarter devices with more powerful computing capabilities and the emergence of new applications/technologics. Despite these facts, the evidence points to a low spectrum utilisation, both in Europe and in the US, even in dense urban areas. Tackling these trends and associated challenges means finding new, better ways to meet the demands for more spectrum by enabling dynamic & flexible spectrum use, and by encouraging cellular operators to share spectrum. This thesis aimed to address some of these challenges. It proposed to avail of the dominant communication system LTE/LTE-Advanced and to enable a systematic approach to spectrum sharing. Its main contributions are as follows: -- The thesis proposed a well-defined spectrum sharing framework that embedded spectrum sharing deep in the LTE-Advanced system by relying on its inherent mechanisms of Carrier Aggregation and Dual Connectivity ...
Keywords: Electronic & Electrical Engineering, Ph.D.; PhD Trinity College Dublin, 2016